Sputtering power e ects on the electrochromic properties of NiO lms - Abenuz Acuña, Juan Ruben; Perez, Israel; Elizalde Galindo, Jose Trinidad; Farias, Rurik; CARRILLO FLORES, DIANA MARÍA; Enriquez Carrejo, Jose Luis; Burrola Gándara, Luis Andrés; Mani Gonzalez, Pierre Giovanni; Sosa, Victor; Gamboa, Fidel (2021)
The effect of sputtering power (=60 W–180 W) on the electrochromic properties of nickel oxide films deposited on ITO-coated glass substrates by the radio frequency magnetron sputtering technique was investigated. Crystalline structure and morphology were assessed by X-ray diffraction and scanning electron microscopy, respectively. The effect of sputtering power on electrochromism of the samples was evaluated with chronoamperometry, cyclic voltammetry, and electrochemical impedance spectroscopy. We used LiClO in a propylene carbonate solution for Li insertion/extraction. The chemical composition of the samples before and after Li intercalation was analyzed by X-ray photoelectron spectroscopy (XPS). We observed the cubic phase of NiO with sputtering power mainly affecting crystallinity and grain size. These in turn affect the electrochromic properties. Coloration efficiency reduces from 24.4 cm2/As to (15.4, 13.7, 16.1) cm2/As, and the reversibility from 40% to 30% as sputtering power increases from 60 W to 180 W. The impedance spectra indicates that ion diffusion is larger for the film grown at 60 W and then goes down for the films deposited at higher sputtering powers. XPS analysis reveals that higher values of promote the formation of nickel hydroxides on the film surface. As a consequence of changes in crystallinity and morphology, the presence of nickel hydroxides increases showing that not only the electrochromic properties of the samples are affected by the sputtering power, but also their chemical composition.